Mediators of Obesity Do Not Influence SARS-CoV-2 Infection or Activation of Primary Human Lung Microvascular Endothelial Cells In Vitro - ter Ellen, Bram M.; Niewold, Jelmer; Flikweert, Antine; Muller Kobold, Anneke C.; Heeringa, Peter; van Meurs, Matijs; Smit, Jolanda M.; van der Voort, Peter H. J.; Rodenhuis-Zybert, Izabela A.; Moser, Jill (Frontiers in Immunology, 2022)
Clinical observations have shown that obesity is associated with the severe outcome of SARS-CoV-2 infection hallmarked by microvascular dysfunction in the lungs and other organs. Excess visceral fat and high systemic levels of adipose tissue (AT) derived mediators such as leptin and other adipokines have also been linked to endothelial dysfunction. Consequently, we hypothesized that AT-derived mediators may exacerbate microvascular dysfunction during of SARS-CoV-2 infection and tested this in a primary human lung microvascular endothelial (HLMVEC) cell model. Our results indicate that HLMVEC are not susceptible to SARS-CoV-2 infection since no expression of viral proteins and no newly produced virus was detected. In addition, exposure to the virus did not induce endothelial activation as evidenced by a lack of adhesion molecule, E-selectin, VCAM-1, ICAM-1, and inflammatory cytokine IL-6 induction. Incubation of endothelial cells with the pro-inflammatory AT-derived mediator, leptin, prior to virus inoculation, did not alter the expression of endothelial SARS-CoV-2 entry receptors and did not alter their susceptibility to infection. Furthermore, it did not induce inflammatory activation of endothelial cells. To verify if the lack of activated phenotype in the presence of adipokines was not leptin-specific, we exposed endothelial cells to plasma obtained from critically ill obese COVID-19 patients. Plasma exposure did not result in E-selectin, VCAM-1, ICAM-1, or IL-6 induction. Together our results strongly suggest that aberrant inflammatory endothelial responses are not mounted by direct SARS-CoV-2 infection of endothelial cells, even in the presence of leptin and other mediators of obesity. Instead, endothelial activation associated with COVID-19 is likely a result of inflammatory responses initiated by other cells. Further studies are required to investigate the mechanisms regulating endothelial behavior in COVID-19 and the mechanisms driving severe disease in obese individuals.